Multiparametric assay of screening for the diagnosis of mycoses of interest in Public Health: standardization of methodology - Kamikawa, Camila Mika; Vicentini, Adriana Pardini (Revista do Instituto Adolfo Lutz, 2022)
The standardization and validation of a multiplex assay requires the combination of important parameters such as sensitivity and specificity, acceptable levels of performance, robustness, and reproducibility. We standardized a multiparametric Dot-blot aimed at the serological screening of paracoccidioidomycosis, histoplasmosis, and aspergillosis. A total of 148 serum were evaluated: 10 from healthy subjects, 36 from patients with paracoccidioidomycosis, 62 from patients with histoplasmosis, and 40 from patients with aspergillosis. It was found that the multiparametric Dot-blot showed a high percentage of cross-reactivity. However, when evaluated individually, in the serological screening of histoplasmosis, a good performance was observed when compared to the double immunodiffusion assay, considered the gold standard test, with 100% co-positivity and 83.3% co-negativity. The performance of serological screening for aspergillosis was not satisfactory when compared to double immunodiffusion, showing 71.4% co-positivity and 100% co-negativity. The evaluation of the stability of nitrocellulose membranes showed that membranes sensitized with H. capsulatum antigen remained stable for 90 days and those sensitized with A. fumigatus antigen for 30 days. We conclude that the use of crude antigens was not suitable for the standardization of the multiparametric Dot-blot assay, due to the high cross-reactivity, and that further tests should be performed with purified proteins.